92.3k views
1 vote
3x square - 6x + 3=0

1 Answer

2 votes

Answer: 1

Explanation:

First you need to multiply 3 x 3 (9), because that's all 3 squared means.

Now the equation should be 9x-6x+3=0

Next we need to combine like terms. Do 9x - 6x which should give you 3x

Now your equations should be 3x+3=0

Now for the somewhat harder part...

Under the three (the one without the x) write -3 and under the zero write the same thing. the +3-3 cancels out so just put a line or something across it.

0-3= -3

so now you should have...

3x=-3 ignore the 3x, at this point it's useless in getting the answer because it would cancel out.

-3 divided by -3 is 1 because a negative (-) divided by a negative (-) equals a positive (+).

The answer should be x = 1

3x square - 6x + 3=0-example-1
User SenseException
by
5.4k points